Soldabilidade dos aços DUAL-PHASE 600 e 800 via processo de soldagem a pontos média freqüência corrente contínua (MFDC) e corrente alternada (AC) - Wolff, Marco Antonio (2008)
Dual-Phase steels have been developed to match the automotive-industry need of highresistance materials that lead to weight reduction and, therefore, reducing emissions. Specifically, in the use Resistance Spot Welding (RSW) process, the Medium Frequency Direct Current (MFDC) equipment has been largely introduced in the automotive industry without, however, scientific studies about its benefits over the Alternating Current (AC) equipment. Thus, this work aims to accomplish a criterious and scientific study on the weldability of 600 and 800 Dual-Phase steels (coated and non-coated), by using RSW both on MFDC and AC equipment. Experimental design was carried out using as factors the equipments, current, welding time, wave shape and electrode geometry (dome and truncated). The assessed responses were spot size, indentation, shear resistance, microhardness, SEM, macro and micro analyses. Weld lobes were obtained, although the fracture mode (partial and interfacial) did not fully matched the standard, mainly on the shear tests. The truncated electrodes led to the best results over the dome ones, even with misalignment on the tip. The MFDC equipment allowed to larger spot growth during lower current levels, which expanded the lobe curves over the ones obtained with the AC equipment. However, the equipment influence was not statistically significative for all cases, although a positive tendency was observed for them. Therefore some open issues still remain concerning the real difference between those two equipments.